2020
DOI: 10.1093/geroni/igaa044
|View full text |Cite
|
Sign up to set email alerts
|

Hopelessness Among Middle-Aged and Older Blacks: The Negative Impact of Discrimination and Protecting Power of Social and Religious Resources

Abstract: Background and Objectives Hopelessness—a state of despair characterized by a negative outlook towards the future and a belief in insurmountable challenges—is a risk factor for major depression, cardiovascular disease, and all-cause mortality among older adults. It is also an understudied consequence of discrimination. Older Blacks disproportionately report experiencing discrimination and, as a result, may be at greater risk of feeling hopeless. However, social and religious resources may prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 82 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…A high level of physical and psychosocial stressors can lead to a number of psychological outcomes, including feelings of hopelessness [ 1 3 ]. Numerous studies have examined the prevalence of and the factors associated with hopelessness in patients with various chronic diseases including cancer [ 4 6 ]. Yet, there has been relatively little research of hopelessness in people living with HIV.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A high level of physical and psychosocial stressors can lead to a number of psychological outcomes, including feelings of hopelessness [ 1 3 ]. Numerous studies have examined the prevalence of and the factors associated with hopelessness in patients with various chronic diseases including cancer [ 4 6 ]. Yet, there has been relatively little research of hopelessness in people living with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…According to the Diagnostic and Statistical Manual of Mental Disorders, 5th edition [DSM-5]; [ 7 ], hopelessness is a symptom of depressive disorders. However, hopelessness may occur independent of depression [ 4 ], or as a precursor to a subtype of depression called hopelessness depression [ 8 ]. Several studies have shown a person can have feelings of hopelessness without feeling depressed [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, some research finds dispositional active coping to be directly associated with less depressive symptoms in Black adolescents (Seaton, Upton, Gilbert, & Volpe, 2014). However, when considering racism‐related stress, removing oneself from the stressor may offer temporary relief (e.g., Brittian et al., 2013), but can lead to long‐term reductions in a sense of agency and greater hopelessness (Mitchell, Gutierrez‐Kapheim, Nguyen, & Al‐Amin, 2020). Some research indicates that coping with racial discrimination through problem solving is associated with less psychological distress (Scott & House, 2005).…”
Section: Mental Health In Black Girls and Womenmentioning
confidence: 99%
“…Finally, Mitchell and colleagues’ (2020) study of hopelessness represents a new and fruitful area of inquiry for studies of discrimination among older Black adults. Black adults have been noted for their higher rates of hopefulness relative to more materially advantaged racial groups (i.e., Whites) and in the face of dire life circumstances.…”
Section: Overview Of Articlesmentioning
confidence: 99%